STUDENTS’ PERCEPTION ON THE USE OF PODCAST TO THE LEARNING OF ENGLISH SPEAKING - Sengang, Agif Estian; Pelenkahu, Noldy; Muntuuntu, Meity (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
This study focused on the students’ perception on the use of podcast to the learning of English speaking. In doing this research, the researcher used questionnaire to be distributed to the students. The researcher used quantitative research as the research method and the collected data were presented in the form of numbers and counted in percentage formula. In distributing this research, the population was the third grade of TKJ students of SMK Cokroaminoto Kotamobagu, which has 5 classes. The researcher took the sample from 3 classes of those 5 classes based on the teacher’s recommendation. There were 3 classes participated in this research which one class consisted of 20 until 25 students. There were total 65 respondents answered the distributed questionnaire. The result of the research showed the domination of positive responses from the respondents of the questionnaire based on the students’ experience in using the podcast as learning media. So, could be concluded that English podcast was effective to use as a media in learning English, especially to practice the speaking skills. The teacher was suggested to always do an improvement in more creative way by using the existing technology and to know what the students need to be fun in various ways of learning especially in learning English also speaking skill practice as well and could be produced the best outcomes from the benefits obtained.